Anaemia among mother-child dyads in India: Trends, drivers, and future projections - Pedgaonker, Sarang; Meher, Trupti; Gupta, Monali; Chakrabarti, Suman; Nguyen, Phuong Hong; Singh, Shri Kant; Dwivedi, Laxmi Kant; Aditi; Scott, Samuel P. (Wiley, 2026)
Anaemia among mothers and their children is a widespread public health challenge with profound consequences for individuals and societies. While anaemia has been studied separately in women and children, there remains a literature gap examining anaemia in mother-child dyads, limiting insights on interventions that may simultaneously address anaemia in both groups. Our study examines trends and drivers of anaemia among mother-child dyads (mothers aged 15–49 years and their children aged 6–59 months; N = 408,342) in India using nationally-representative data from 2006 to 2021 and estimates the potential future reduction in anaemia among mother-child dyads based on changes in selected drivers. We employed descriptive statistics, multivariable logistic regression and population attributable fraction (PAF) analysis. The co-occurrence of anaemia among mothers-child dyads changed very slightly, from 35% in 2006% to 33% in 2016 and to 37% in 2021. Subnational analyses revealed varying trends by states, with Delhi showing the highest increase (17%–32%) and Sikkim the largest decrease (29%–16%) between 2006 and 2021. Maternal education, regular consumption of nonvegetarian food and green leafy vegetables, consumption of iron folic acid supplements, utilization of government health services, and improved sanitation at both household and community levels were associated with lower likelihood of anaemia among mother-child dyads. The cumulative PAF suggested that addressing these factors collectively could reduce anaemia prevalence among mother-child dyads by 18% to 28% (under different scenarios) by 2030. The study underscores the need for comprehensive, multi-sectoral interventions targeting both maternal and child health to effectively combat anaemia in mother-child dyads.